2017
DOI: 10.1590/2179-8087.033916
|View full text |Cite
|
Sign up to set email alerts
|

Litterfall and Nutrient Dynamics in a Mature Atlantic Rainforest in Brazil

Abstract: We assessed litterfall and nutrient cycling in an old-growth Atlantic rainforest in southern Brazil. Plant litter collected monthly was separated into: leaves, twigs, reproductive organs, and fragments, and dried, weighed, and ground. Determination of carbon, nitrogen, phosphorus, potassium, calcium, magnesium, and sodium contents of different litter fractions was also performed. The total deposition was 8.44 Mg -1 ha -1 year -1 , with a higher proportion of leaves fraction. Litterfall predominated in spring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(44 reference statements)
1
2
0
7
Order By: Relevance
“…A maior deposição anual foi para a área FS-5, seguida de FS-2 estatisticamente superiores a FS-4, demonstrando que não houve relação de acréscimo ou decréscimo na produção total de serapilheira nas formações secundárias em decorrência da idade e, logo, esta variável não foi um fator de diferenciação na produção de serapilheira entre florestas secundárias deste estudo. A produção de serapilheira total ficou estimada entre 4,9 a 10,1 (ROCHA, 2006;DICKOW et al, 2012;BIANCHIN et al, 2016;SLOBODA et al, 2017).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A maior deposição anual foi para a área FS-5, seguida de FS-2 estatisticamente superiores a FS-4, demonstrando que não houve relação de acréscimo ou decréscimo na produção total de serapilheira nas formações secundárias em decorrência da idade e, logo, esta variável não foi um fator de diferenciação na produção de serapilheira entre florestas secundárias deste estudo. A produção de serapilheira total ficou estimada entre 4,9 a 10,1 (ROCHA, 2006;DICKOW et al, 2012;BIANCHIN et al, 2016;SLOBODA et al, 2017).…”
Section: Resultsunclassified
“…As tipologias florestais possuem um padrão na distribuição do aporte de serapilheira ao longo do ano, que pode ser influenciado por diversos fatores como: fenologia das espécies presentes, condições meteorológicas, estágio sucessional e posição no relevo (GIÁCOMO, 2009). Embora existam diversos estudos relacionados ao aporte de nutrientes na Floresta Atlântica (CALDEIRA et al, 2008;CALVI et al, 2009;SILVA e VILLELA, 2015;SLOBODA et al, 2017), são poucos os que relatam a transferência de nutrientes em florestas secundárias com diferentes idades.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The references found in the specific literature with respect to annual amount of litterfall in Ombrophilous Dense Forest vary according to forest formation, ranging from 5.4 to 12.2 Mg ha -1 yr -1 in Submontane Ombrophilous Dense Forest (ARAÚJO et al, 2006;DICKOW et al, 2012;BIANCHIN et al, 2016;SLOBODA et al, 2017), from 4.9 to 5.6 Mg ha -1 yr -1 in Montane (GOMES et al, 2010;FREIRE et al, 2014), and from 6.1 to 7.1 Mg ha -1 yr -1 in Mixed Ombrophilous Forest (FIGUEIREDO FILHO et al, 2005;ANTONELI;THOMAZ, 2012;SANQUETTA et al, 2016). In studies carried out in old-grown forests in the north coast of Parana state, litterfall was estimated at 8.4 Mg ha -1 yr -1 (SLOBODA et al, 2017), and in advanced secondary forests in the southern region of Santa Catarina at 7.5 to 10.55 Mg ha -1 yr -1 (CITADINI-ZANETTE, 1995;SANTOS, 1997;ROSSO, 2011), being close to that sampled in AR in the present study, with 8.13 Mg ha -1 yr -1 . The results of the study of litterfall in the south of Santa Catarina showed that there is a marked deposition in the months of October and November for the primary forest fragment (CITADINI-ZANETTE, 1995;SANTOS, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Fração galhos finos --------kg ha -1 -------- A estimativa do aporte anual de serapilheira da fração galhos encontrada nesse trabalho foi abaixo do que observado por Sloboda et al (2017), em uma área de Floresta Atlântica, onde a fração representou 12% do total, ainda assim, considerado uma baixa proporção em relação a fração folhas, que representa a maior parte da serapilheira na maioria dos estudos (KÖNIG et al, 2002;FIGUEIREDO FILHO et al, 2003;CUNHA NETO et al, 2013;BIANCHIN et al, 2016;SLOBODA et al, 2017). Figueiredo Filho et al (2003), afirmam que,normalmente as folhas são responsáveis por mais de 50% da serapilheira produzida em uma floresta.…”
Section: Serapilheira Totalunclassified